Method for improving bending resistance of optical OCA (Optical Clear Adhesive)
By using block copolymer optical glue and standing at high temperature, the problem of softening and yellowing of optical OCA glue in high temperature environment is solved, and the high temperature bending resistance and stability of the optical device are achieved.
Patent Information
- Application Number
- CN202311847506.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-02-14
AI Technical Summary
The existing optical OCA glue is prone to softening and yellowing in high temperature environments, resulting in a degradation of structural stability and performance of optical devices, making it difficult to meet the bending resistance requirements in high temperature environments.
Block copolymer is used as optical glue, and by bonding it to the optical element and standing in an environment of 35-100°C for 1-30 days, the bonding strength and folding resistance of the glue layer are enhanced to avoid yellowing.
It significantly improves the folding resistance and high temperature stability of the optical device, ensuring that it does not turn yellow under high temperature environments, and maintains excellent light transmittance and toughness.
Smart Images

Figure CN119432274A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical adhesives, and in particular to a method for improving the bending resistance of optical OCA adhesives. Background Art
[0002] With the continuous advancement of science and technology, optical devices are increasingly used in various fields, such as mobile devices, flexible displays, etc. However, in these applications, optical devices often need to face various complex mechanical stresses, especially folding and bending stresses, which puts higher requirements on the reliability and stability of the devices. In order to meet this challenge, improving the folding resistance of optical devices has become one of the important research directions.
[0003] In the existing optical device manufacturing technology, traditional bonding methods often have difficulty in maintaining excellent optical performance while achieving sufficient folding resistance. Although low-temperature adhesive bonding can maintain the excellent performance of optical devices, when faced with mechanical stress such as bending and folding, the adhesive layer is prone to peeling, cracking and other problems, thus affecting the service life of the device. While improving the mechanical stability of the adhesive layer, it often leads to a decrease in optical performance, limiting the application range of the device.
[0004] In the preparation process of existing optical adhesives, additives such as tackifying resins are often added to improve the peel strength of optical devices, thereby effectively preventing undesirable phenomena such as debonding during frequent folding operations. This strategy aims to enhance the adhesion between optical adhesives and other components, thereby ensuring the stability and durability of the device.
[0005] For example, CN116239992 A discloses a bending-resistant organic silicon OCA optical adhesive and its preparation method, which belongs to the field of organic silicon materials. According to the weight percentage, it includes the following components: 10-20% methyl vinyl polysiloxane; 25-35% VMQ resin; 2-3% tackifying resin; 1-2.5% silane coupling agent; 1.5-2.5% hydrogen-containing silicone oil; 1-2.5% cross-linking agent; 3-5% catalyst; 0.05-0.25% inhibitor; 35-45% toluene. This application uses methyl vinyl polysiloxane, VMQ resin and silane coupling agent to mix and prepare the organic silicon main body, and obtains the organic silicon OCA optical adhesive with excellent bending resistance, high peel strength and good light transmittance through hydrogen-containing silicone oil addition and curing. The preparation method is simple to operate and has good prospects for industrial promotion.
[0006] However, although the tackifying resin improves the adhesion performance of the adhesive layer to some extent, it brings a series of new challenges. It is worth noting that due to its special chemical structure, the tackifying resin usually softens in high-temperature use environments. This softening phenomenon may cause the optical device to lose its original structural stability in a high-temperature environment, and even cause problems such as changes in its chemical structure. What is more worrying is that the tackifying resin has a low softening point and is prone to yellowing under high temperature conditions. This yellowing phenomenon not only affects the appearance of the optical device, but may also have a negative impact on its performance, thereby restricting its reliability and application range in high-temperature environments.
[0007] Therefore, although tackifying resin has a positive effect in improving peel strength, its performance in high temperature environments has become a difficult problem that needs to be solved. In order to achieve optical devices that can still maintain stability in high temperature environments, we need to find ways to enhance the bonding and bending resistance of optical adhesives.
[0008] CN115895467 A discloses a method for preparing an optical OCA glue and an application of the optical OCA glue in a folding screen of a mobile phone. The optical OCA glue comprises the following raw materials in parts by weight: 40-60 parts of lauryl methacrylate, 30-50 parts of isooctyl acrylate, 2-5 parts of acrylic acid, 0.2-0.6 parts of a primary cross-linking agent, 0.5-5 parts of azobisisobutyronitrile, 0.1-0.3 parts of an auxiliary cross-linking agent, and 0.01-0.04 parts of p-toluenesulfonic acid. A primary cross-linking agent containing a disulfide bond in the main chain and an auxiliary cross-linking agent containing an acyl brown group in the main chain are prepared as raw materials for a polyacrylic acid adhesive, so that the prepared optical OCA latex has a higher cross-linking density, so that the optical OCA glue has excellent bending resistance and high temperature resistance, but the bending resistance of the product is not very ideal. Summary of the invention
[0009] In view of the problem that optical devices prepared by low-temperature optical OCA glue in the prior art have poor bending resistance, the present invention provides a method for preparing optical OCA glue with stronger connection performance between optical elements, which can effectively improve the folding resistance of the device. The product has excellent toughness and light transmittance, does not yellow at high temperature, and the preparation method is simple and easy to operate.
[0010] To achieve the above object, the technical solution adopted by the present invention is:
[0011] A method for improving the bending resistance of optical OCA adhesive, comprising the steps of: bonding the optical adhesive to the functional layer of an optical element and leaving it to stand in an environment of 35-100° C. for 1-30 days;
[0012] The optical adhesive is a block copolymer, and the general structural formula of the block copolymer is M1-b-M2-b-M3...-bM j, where j ranges from 3 to 11; where M1, M2, M3, ... j It is a comonomer in the block copolymer, and the number average molecular weight of the block copolymer is 80,000 to 800,000 g / mol; the comonomer includes a soft monomer, a hard monomer or a functional monomer; and the mass content of the soft monomer, the hard monomer and the functional monomer in the block copolymer is 70 to 98%, 2 to 30% and 0 to 5% respectively.
[0013] Based on a low-modulus, high-strength and high-transparency optical adhesive, the applicant further discovered that after bonding it to an optical element and then subjecting it to a heating and standing treatment, the bonding strength of the interface between the two can be effectively improved. The longer the placement time and the higher the treatment temperature, the stronger the bonding strength. The treated optical device can be folded 50,000 to 300,000 times repeatedly without obvious creases on the surface, and there is no obvious yellowing after high-temperature treatment, overcoming the yellowing problem of adding tackifying resins in a high-temperature environment. The treatment method is simple and easy to handle, and mainly utilizes the long-term standing treatment of the soft adhesive at a high temperature, making it softer in shape and increasing the effective bonding area between the adherend and the adhesive, thereby improving the peel strength.
[0014] The hard monomer includes one or more of styrene, methyl acrylate, methyl methacrylate, acrylamide, acrylonitrile and vinyl acetate, and its glass transition temperature ranges from 60 to 150° C. The microphase separation formed by the hard monomer can provide a rebound network for the optical adhesive, thereby improving the bending resistance of the optical adhesive.
[0015] The soft monomer includes one or more of ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isooctyl acrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isooctyl methacrylate, butadiene, isoprene, ethylene-butene and methacrylic acid, and the glass transition temperature ranges from -90 to -30°C; the soft monomer mainly provides low modulus for the optical adhesive.
[0016] The functional monomers include one or more of methacrylic acid, acrylic acid, itaconic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylenedimethylamine methacrylate, methacrylic acid amine, N-hydroxymethyl acrylamide, glycidyl methacrylate and maleic anhydride. The carboxylate radical in the functional monomers can improve the cohesion and peel strength of the optical adhesive.
[0017] The Young's modulus of the optical adhesive is below 500 kPa. Preferably, the Young's modulus of the optical adhesive is below 200 kPa. The optical adhesive has a lower modulus and can better increase the contact area after being placed at high temperature.
[0018] The optical adhesive has a light transmittance of more than 80%, a creep resilience of more than 30%, a strain recovery rate of more than 30%, and a shear modulus of less than 100 kPa.
[0019] The thickness of the optical adhesive is 25-200 μm, and the selected thickness is the mainstream optical adhesive thickness in the current market.
[0020] The optical element functional layer includes one or more of optical glass, foldable screen glass, cover window, touch sensor, circular polarizer, and light-emitting layer.
[0021] Preferably, the optical element can undergo repeated bending or folding with a bending radius of 0.5 to 10 mm without significant change in appearance.
[0022] The peel strength between the optical adhesive and the functional layer of the optical element after being left to stand by the above method is 7.0 N / 25 mm or more, preferably 8 N / 25 mm or more, 9 N / 25 mm or more, 10 N / 25 mm or more, or 11 N / 25 mm or more.
[0023] Further preferably, the method for improving the bending resistance of optical OCA glue comprises the steps of: bonding the optical glue to the functional layer of the optical element and placing the adhesive in an environment of 50-100°C for 3-15 days; after standing for a long time at a relatively high temperature, the bonding strength is higher and the folding resistance is better.
[0024] Preferably, when the optical adhesive is bonded to the functional layer of the optical element, the generation of bubbles and wrinkles should be avoided as much as possible.
[0025] The optical adhesive is prepared by reversible addition-fragmentation chain transfer emulsion polymerization or reversible addition-fragmentation chain transfer solution polymerization.
[0026] The preparation method of the optical adhesive comprises the steps of:
[0027] Step 1, dissolving an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent in water, then adding a hard monomer and stirring until the mixture is uniformly mixed, adding a first initiator at 70-90° C., reacting for 1-3 hours to obtain a homopolymer, and the homopolymer is stably dispersed in water in the form of particles to form a latex;
[0028] Step 2, adding sodium hydroxide aqueous solution, soft monomer and water, adding a second initiator at 40-60° C., reacting for 4-10 hours in an anaerobic environment, and then adding a hard monomer, reacting for 5-10 hours in an anaerobic environment to obtain a latex of a block copolymer;
[0029] Step 3, adding hydrogen peroxide and hydrochloric acid to the latex of the block copolymer, heating to 40-60° C. and reacting for 1.5-3 hours; then washing and drying the precipitated product to obtain the block copolymer;
[0030] Step 4, the block copolymer is dissolved in a dispersion medium, coated into a film in an argon environment, dried, and the upper and lower layers are laminated with a light release film and a heavy release film to obtain an OCA optical adhesive;
[0031] Step 5, tear off the release film on the upper layer of the optical adhesive, and laminate the optical element functional layer onto the optical adhesive; then tear off the release film on the lower layer of the optical adhesive, and laminate the optical element functional layer onto the optical adhesive to obtain a multilayer optical element;
[0032] Step 6: placing the multi-layer optical element in an environment of 35-100° C. for 1-30 days to achieve close connection of the multi-layer optical element and improve the bending resistance.
[0033] The chemical structural formula of the amphiphilic macromolecular reversible addition fragmentation chain transfer agent (RAFT agent) is: R-(M n1 -bN n2 )-X; wherein R is isopropanoyl, acetyl, 2-cyanoacetyl or 2-aminoacetyl; M n1 In the formula, M is a methacrylic acid monomer or an acrylic acid monomer unit, n1 is the average polymerization degree of M, and n1 ranges from 10 to 30; N n2 In the method, N is a styrene monomer, n-butyl acrylate monomer, methyl acrylate, isooctyl acrylate or methyl methacrylate monomer unit, n2 is the average polymerization degree of N, and the range of n2 is 1 to 8; the X group is an alkyl dithioester group or an alkyl trithioester group; and the amount of the RAFT agent added is 0.1-1.0 wt% of the combined mass of all copolymerized monomers.
[0034] The dispersion medium includes any one or more of diethyl ether, methyl tert-butyl ether, tetrahydrofuran, methyl ethyl ketone, ethyl acetate and methyl propionate.
[0035] The first initiator is any one or more of ammonium persulfate, potassium persulfate, hydrogen peroxide and hydrogen peroxide derivatives; the mass of the first initiator is 1 / 2-1 / 30 of that of the RAFT agent;
[0036] The second initiator is any one or more of azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, sodium hydrogen persulfate / potassium persulfate redox initiator and sodium persulfate / ammonium persulfate redox initiator, and the mass dosage is 1 / 2-1 / 30 of that of the macromolecular RAFT agent.
[0037] The mass concentration of hydrogen peroxide added in step 3 is 20-30wt%, and the mass concentration of hydrochloric acid is 5-10wt%;
[0038] In step 3, the volume ratio of polymer latex, hydrogen peroxide and hydrochloric acid is 2:0.5-2:1-3, preferably 2:1:2.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention introduces a heating and long-term static treatment during the optical adhesive bonding process, so that the optical device obtains stronger mechanical stability and folding resistance after the adhesive layer is cured. Compared with the traditional method, this method can not only improve the folding resistance of the optical device, but also maintain its excellent optical performance, providing a more stable and reliable solution for the practical application of the optical device. This method is applicable to different types of optical devices, whether flexible optical elements or rigid optical elements. The processing method is simple and easy to operate, and can be applied to mobile devices, flexible displays and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the appearance picture of the optical element prepared in Examples 1-3 after the folding resistance test.
[0042] Figure 2 Graph showing the optical properties of the optical elements obtained in Examples 1-3.
[0043] Figure 3 It is a diagram showing the appearance color results of the optical elements prepared in Examples 1-3. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0045] The raw materials used in the following specific embodiments are all purchased from the market.
[0046] Preparation of poly(styrene-b-isooctyl acrylate-b-styrene) block copolymer:
[0047] The optical adhesive used is prepared according to Example 1 of ZL202210797594.8 (authorization announcement number: CN115260921B), wherein the soft monomer is isooctyl acrylate, accounting for 90%, and the hard monomer is styrene, accounting for about 10%. The Young's modulus of the optical adhesive is 162.7 kPa, the rebound rate exceeds 90%, and the peel strength is 6.4 N / 25 mm.
[0048] The above-mentioned poly(styrene-b-isooctyl acrylate-b-styrene) block copolymer is used as an optical adhesive to improve the bonding strength with optical glass. The specific steps are as follows:
[0049] Step 1, tear off the release film on the poly(styrene-b-isooctyl acrylate-b-styrene) block copolymer optical adhesive, and attach the optical glass to the optical adhesive to avoid the generation of bubbles and wrinkles;
[0050] Step 2, tear off the release film at the bottom of the poly(styrene-b-isooctyl acrylate-b-styrene) block copolymer optical adhesive, and attach the optical glass to the optical adhesive, also avoiding the generation of bubbles and wrinkles;
[0051] Step 3, after the bonding is completed, the optical element is obtained and placed in an environment of 50°C for 1-30 days. The glass strength between the optical glue and the optical glass is tested before, 1 day, 7 days, 14 days and 30 days after placement, and the folding resistance of the optical element is tested.
[0052] The number average molecular weight of the polymer was characterized using a gel chromatography permeameter (GPC, Water 1525 / 2414, Waters, USA). The sample needed to be prepared as a 3 mg / mL tetrahydrofuran solution before testing and filtered using a 0.45 μm GHP filter to prevent large-sized impurities from clogging the chromatographic column. The test used tetrahydrofuran (THF) as the mobile phase, polystyrene (PS) as the standard sample, and the test temperature was 30°C.
[0053] The mechanical tensile properties of the film were measured by a universal material testing machine (UTM 2502, Shenzhen Sansi Zongheng). The test method was in accordance with the standard GB16421-1996, and the samples were cut into standard dumbbell-shaped specimens. The tensile rate of the testing machine was 20 mm / min, and the test of each sample was repeated at least three times. The tensile strength, elongation at break, and elastic modulus results were the average of the three test results.
[0054] The strain recovery rate of the film was characterized by a dynamic mechanical analyzer with environmental control (DMA, TA Q800, TA Instruments, USA). The sample was cut into 20mm×5mm strips. The test temperature was 25℃, and the mode was tensile mode. At the beginning of the test, the sample was stretched to the set strain within 1s, at which time the strain was recorded as ε0 and maintained for 1h; then the applied force was unloaded and maintained for 1h, at which time the strain was recorded as ε 60 The strain recovery rate b is calculated according to the following formula.
[0055]
[0056] The peel strength was tested by an adhesive shear strength tester (KJ-1066A). The optical pressure-sensitive adhesive film was cut into strips with a width of 25 mm and a length of about 300 mm. The test method adopted GB / T2792-2014, and the test of each sample was repeated at least three times.
[0057] The folding resistance test of optical adhesive was measured by a temperature and humidity bending durability tester (Beijing Wohua Huitong Measurement and Control Technology Co., Ltd.). The sample was then cut into strips with a width of 5 cm and a length of 20 cm, and then the longer sides were fixed on the tester with tape, the bending angle was set to 180°, the test frequency was 60 times / min, and the bending radius was set to 3 mm as needed, with debonding, breakage and obvious creases as the end point.
[0058] The test results of the glass strength between the optical glue and the optical glass and the folding resistance of the optical components at different times are shown in Table 1. It can be seen that after a long period of placement, the glass strength between the optical glue and the glass increases, the connection is tighter, and the folding resistance is significantly improved. After 14 days of placement, the peel strength and folding resistance are not significantly improved, but are still improved to a certain extent.
[0059] Table 1 Peel strength and folding resistance of the optical element of Example 1 at different storage times at 50°C
[0060] Placement time Peel strength / (N / 25mm) Folding resistance times / times Day 0 6.8 10,000 1 day 7.8 30,000 7 days 11.5 200,000 14 days 12.0 280,000 30 days 12.5 300,000
[0061] Example 2
[0062] The optical adhesive prepared from poly(styrene-b-isooctyl acrylate-b-styrene) triblock copolymer and poly(styrene-b-isooctyl acrylate) copolymer has the following preparation process:
[0063] The optical adhesive used is prepared according to Example 2 of ZL202210797594.8 (authorization announcement number: CN115260921B).
[0064] The soft monomer is isooctyl acrylate, accounting for 93%, and the hard monomer is styrene, accounting for about 7%. The Young's modulus of the optical adhesive is 132.4.7 kPa, the rebound rate exceeds 90%, and the peel strength is 9.40 N / 25 mm.
[0065] The optical adhesive prepared by blending the above-mentioned poly(styrene-b-isooctyl acrylate-b-styrene) triblock copolymer and poly(styrene-b-isooctyl acrylate) copolymer was used for bonding with optical glass. The bonding process was the same as the steps in Example 1. After bonding, the optical element was placed at room temperature, 40°C, 60°C, 80°C and 100°C for 3 days, and the glass strength between the optical adhesive and the optical glass was tested. The folding resistance of the optical element was also tested. The results are shown in Table 2.
[0066] It can be seen from Table 2 that under the same processing time, the higher the processing temperature, the higher the number of folding resistance. This is because high temperature can soften the optical pressure-sensitive adhesive, thereby increasing the contact area between the pressure-sensitive adhesive and the adherend, thereby increasing the peel strength, thereby increasing the number of folding resistance of the optical adhesive.
[0067] Table 2 Peel strength and folding resistance of the optical element of Example 2 after being placed at different temperatures for 3 days
[0068] Storage temperature / ℃ Peel strength / (N / 25mm) Folding resistance times / times normal temperature 7.1 20,000 40 8.2 50,000 60 9.8 150,000 80 10.0 300,000 100 12.1 300,000
[0069] Example 3
[0070] The preparation process of poly(styrene-b-isooctyl acrylate-b-styrene) block copolymer optical adhesive is as follows:
[0071] The optical adhesive used was prepared with reference to Example 1 of ZL202210797594.8 (authorization announcement number: CN115260921B), in which the mass fractions of hard monomers and soft monomers added were different, and the molecular weight of the prepared block copolymer was shown in Table 3.
[0072] The soft monomer is isooctyl acrylate, accounting for 70-97%; the hard monomer is styrene, accounting for 3-30%. The Young's modulus, strain recovery rate and peel strength of the optical adhesive refer to Table 3 /
[0073] Optical adhesive A, optical adhesive B, optical adhesive C, optical adhesive D, and optical adhesive E were obtained respectively, and the molecular weight, modulus test method, and strain recovery rate test method of each block were the same as those of Example 1.
[0074] The above optical adhesives AE are used to bond with optical glass respectively, and the bonding process is the same as the steps in Example 1. After bonding, the optical element is placed in an environment of 50°C for 7 days, and the glass strength between the optical adhesive and the optical glass is tested, and the folding resistance of the optical element is also tested. The modulus of each block of different optical adhesives, strain recovery rate and performance data after treatment are shown in Table 3.
[0075] As can be seen from Table 3, under the same processing time and the same processing temperature, due to the different composition structures of the optical adhesive used, the peel strength between the optical adhesive and the glass after treatment is quite different, and the folding resistance is also quite different. This is because when the modulus is high, the contact area between the optical adhesive and the adherend does not increase much after passing through, resulting in the peel strength cannot be fully improved.
[0076] Table 3 Modulus, strain recovery rate and performance data of each block of different optical adhesives after treatment
[0077]
[0078] The optical elements prepared in Examples 1-3 were tested for transmittance and spectral haze. The optical transmittance of the OCA optical pressure-sensitive adhesive after static treatment was measured by an ultraviolet spectrophotometer (Cary5000, Agilent, USA), and the sample was cut into a circle with a diameter of 2 mm. The optical adhesive and optical glass raw materials used were used as test samples and reference samples, respectively. The wavelength scanning range was 300-800 nm. Before the test, the glass sheet was used as the background for transmittance scanning. Then, the upper release protective film was torn off the adhesive film in the optical element after static treatment and attached to the glass sheet, and then the lower release protective film was torn off, and the transmittance scan was performed again.
[0079] The optical and color properties of OCA optical pressure-sensitive adhesive were measured by a spectral haze meter (Yuanfang HAM-300), with a scanning light source of D65 and a scanning angle of 10°. The upper release layer of the prepared film was torn off and attached to the test platform, and then the lower release layer was torn off for testing.
[0080] Figure 1 The picture in the middle is of the optical element prepared in Example 1 after being placed for 14 days and subjected to 200,000 folding resistance tests, and there are no obvious creases on its surface. Example 2 refers to the picture of the optical element prepared in Example 2 after being placed at 40°C for 4 days and subjected to 50,000 folding resistance tests. It can be found that there is clear debonding. This indicates that the time is insufficient, resulting in low peel strength and stratification between the optical adhesive and the adherend; Example 3 refers to the optical element prepared by optical adhesive D, which is placed at 50°C for 7 days and subjected to 200,000 folding resistance tests. There are no obvious creases, indicating that the peel strength of the optical adhesive can be improved at appropriate temperature and time to meet the folding resistance requirements.
[0081] Figure 2 The optical performance results of the optical element prepared in Example 1 after being placed at 50°C for 14 days, the optical element prepared in Example 2 after being placed at 40°C for 4 days, and the optical element prepared by optical adhesive D in Example 3 after being placed at 50°C for 7 days. The optical transmittance of the optical pressure-sensitive adhesive after the bonding process does not change significantly compared to the optical pressure-sensitive adhesive without high-temperature bonding, and both are greater than 99%.
[0082] Figure 3 These are the color result graphs of the optical element prepared in Example 1 after being placed at 50°C for 14 days, the optical element prepared in Example 2 after being placed at 40°C for 4 days, and the optical element prepared by optical adhesive D in Example 3 after being placed at 50°C for 7 days. There is no obvious yellowing phenomenon of the optical pressure-sensitive adhesive after the high-temperature bonding process.
Claims
1. A method for improving the bending resistance of optical OCA glue, characterized in that: The method comprises the steps of: bonding the optical adhesive to the functional layer of the optical element and placing the adhesive in an environment of 35-100° C. for 1-30 days; The optical adhesive is a block copolymer, and the general structural formula of the block copolymer is M1-b-M2-b-M3...-bM j , where j ranges from 3 to 11; where M1, M2, M3, ... j It is a comonomer in the block copolymer, and the number average molecular weight of the main matrix block copolymer is 80,000 to 800,000 g / mol; the comonomer includes a soft monomer, a hard monomer or a functional monomer; and the mass content of the soft monomer, the hard monomer and the functional monomer in the block copolymer is 70 to 98%, 2 to 30% and 0 to 5% respectively.
2. The method for improving the bending resistance of optical OCA glue according to claim 1, characterized in that: The thickness of the optical adhesive is 25-200 μm.
3. The method for improving the bending resistance of optical OCA adhesive according to claim 1, characterized in that: The optical element functional layer includes one or more of optical glass, foldable screen glass, cover window, touch sensor, circular polarizer, and light-emitting layer.
4. The method for improving the bending resistance of optical OCA adhesive according to claim 1, characterized in that: The hard monomer includes one or more of styrene, methyl acrylate, methyl methacrylate, acrylamide, acrylonitrile and vinyl acetate, and the glass transition temperature thereof is in the range of 60 to 150° C.; The soft monomer comprises one or more of ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isooctyl acrylate, octyl acrylate, 2-propylheptyl acrylate, isononyl acrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isooctyl methacrylate, butadiene, isoprene, ethylene-butene and methacrylic acid, and the glass transition temperature ranges from -90 to -30°C; The functional monomers include one or more of methacrylic acid, acrylic acid, itaconic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylenedimethylamine methacrylate, methacrylic acid amine, N-hydroxymethyl acrylamide, glycidyl methacrylate and maleic anhydride.
5. The method for improving the bending resistance of optical OCA adhesive according to claim 1, characterized in that: The Young's modulus of the optical adhesive is below 500 kPa.
6. The method for improving the bending resistance of optical OCA adhesive according to claim 1, characterized in that: The optical adhesive has a light transmittance of more than 80%, a creep resilience of more than 30%, a strain recovery rate of more than 30%, and a shear modulus of less than 100 kPa.
7. The method for improving the bending resistance of optical OCA adhesive according to claim 1, characterized in that: The peel strength between the optical adhesive and the functional layer of the optical element after standing is above 7.0N / 25mm.
8. The method for improving the bending resistance of optical OCA adhesive according to claim 1, characterized in that: The optical adhesive is prepared by reversible addition-fragmentation chain transfer emulsion polymerization or reversible addition-fragmentation chain transfer solution polymerization.
9. The method for improving the bending resistance of optical OCA adhesive according to claim 1 or 8, characterized in that: The preparation method of the optical adhesive comprises the steps of: Step 1, dissolving an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent in water, then adding a hard monomer and stirring until the mixture is uniformly mixed, adding a first initiator at 70-90° C., reacting for 1-3 hours to obtain a homopolymer, and the homopolymer is stably dispersed in water in the form of particles to form a latex; Step 2, adding sodium hydroxide aqueous solution, soft monomer and water, adding a second initiator at 40-60° C., reacting for 4-10 hours in an anaerobic environment, and then adding a hard monomer, reacting for 5-10 hours in an anaerobic environment to obtain a latex of a block copolymer; Step 3, adding hydrogen peroxide and hydrochloric acid to the latex of the block copolymer, heating to 40-60° C. and reacting for 1.5-3 hours; then washing and drying the precipitated product to obtain the block copolymer; Step 4, the block copolymer is dissolved in a dispersion medium, coated into a film in an argon environment, dried, and the upper and lower layers are laminated with a light release film and a heavy release film to obtain an OCA optical adhesive; Step 5, tear off the release film on the upper layer of the optical adhesive, and laminate the optical element functional layer onto the optical adhesive; then tear off the release film on the lower layer of the optical adhesive, and laminate the optical element functional layer onto the optical adhesive to obtain a multilayer optical element; Step 6: placing the multilayer optical element in an environment of 35-100° C. for 1-30 days.
10. The method for improving the bending resistance of optical OCA adhesive according to claim 9, characterized in that: The dispersion medium includes any one or more of diethyl ether, methyl tert-butyl ether, tetrahydrofuran, methyl ethyl ketone, ethyl acetate and methyl propionate; and / or, the first initiator is any one or more of ammonium persulfate, potassium persulfate, hydrogen peroxide and hydrogen peroxide derivatives; And / or, the second initiator is any one or more of azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, sodium persulfate / potassium persulfate redox initiator and sodium persulfate / ammonium persulfate redox initiator.
Citation Information
Patent Citations
An OCA optical pressure-sensitive adhesive and its preparation method
CN115260921B
Preparation method of optical OCA (Optical Clear Adhesive) and application of optical OCA in folding screen of mobile phone
CN115895467A
Bending-resistant organic silicon OCA optical adhesive and preparation method thereof
CN116239992A